The Effectiveness of Mathematics Learning Through the Implementation of the Team Assisted Individualization (TAI) Cooperative Model for Class VIII B Students of MTS Al-Bashirah Makassar - Marlina; Minggi, Ilham; Wahyuddin, (Jurnal Keguruan dan Ilmu Pendidikan (JKIP), 2023)
This research aimed to determine the effectiveness of Team Assisted Individualization (TAI) type of Cooperative Model in learning Mathematics for students of Grade VIII B MTs. Al-Bashirah Makassar. The type of this research was a pre-experimental research with one group pretest and posttest design. This research referred to the effectiveness criteria of learning. The research was conducted on students of Grade VIII B MTs. Al-Bashirah Makassar totaling 20 students. The results of this research showed that: (1) the students' mean score after applying Team Assisted Individualization type of cooperative model was 70.25 and it was in the fair category. From the results it was obtained that 18 or 90% students achieved individual completeness, 2 or 10% students did not achieve individual completeness was classically achieved with a normalized gain value of 0.47 in the medium category. (2) the mean percentage of students' activity was 84.17% active in learning mathematics. (3) the mean percentage of students giving a positive response was 95%. Therefore, learning mathematics was effective by using Team Assisted Individualization type of cooperative model of students grade VIII B MTs Al-Bashirah Makassar.